2023
DOI: 10.1038/s41467-023-38221-1
|View full text |Cite
|
Sign up to set email alerts
|

Translational reprogramming as a driver of antimony-drug resistance in Leishmania

Abstract: Leishmania is a unicellular protozoan that has a limited transcriptional control and mostly uses post-transcriptional regulation of gene expression, although the molecular mechanisms of the process are still poorly understood. Treatments of leishmaniasis, pathologies associated with Leishmania infections, are limited due to drug resistance. Here, we report dramatic differences in mRNA translation in antimony drug-resistant and sensitive strains at the full translatome level. The major differences (2431 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…Interestingly, Andrade et al reported a downregulation of processes related to translation in L. infantum Sb-resistant strains, including rRNA processing, ribosome biogenesis, ribonucleoprotein complex, nucleosome assembly, and overall translation (Andrade et al, 2020). Our results are consistent with recent studies on L. tropica antimony-resistant strains, which also revealed a notable increase in proteins linked to translation (Gutierrez Guarnizo et al, 2023). This implies that changes in ribosomal proteins and translation initiation factors could be pivotal in the observed translational alterations, possibly serving as preemptive adaptations to drug exposure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, Andrade et al reported a downregulation of processes related to translation in L. infantum Sb-resistant strains, including rRNA processing, ribosome biogenesis, ribonucleoprotein complex, nucleosome assembly, and overall translation (Andrade et al, 2020). Our results are consistent with recent studies on L. tropica antimony-resistant strains, which also revealed a notable increase in proteins linked to translation (Gutierrez Guarnizo et al, 2023). This implies that changes in ribosomal proteins and translation initiation factors could be pivotal in the observed translational alterations, possibly serving as preemptive adaptations to drug exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Gutierrez Guarnizo et al, 2023). Integrative omics studies are necessary to study this phenomenon since an integrative comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…However, these compounds have a narrow therapeutic window, and resistant Leishmania strains threaten their efficacy. Recently, our group uncovered that antimony drug resistance is established not only through the acquisition of genetic mutations, as shown in earlier studies, but through the reprogramming of translation that coordinates the lipidome and metabolome remodeling to counteract the drug [ 122 , 123 , 124 ]. Miltefosine, paromomycin, and amphotericin B are other compounds used to treat leishmaniasis, but they also have toxicity issues and face resistance challenges [ 125 , 126 ].…”
Section: Mechanisms Of Persistence In Leishmania Sppmentioning
confidence: 99%